Estudo da toxicidade e genotoxicidade induzidas por diferentes nanopartículas in vivo - Andrade, Laise Rodrigues de (2012)
The rapid advancement of nanotechnology has created a vast array of nanoparticles promising for industrial, energy and environmental sectors. Furthermore, many biological applications have been proposed for the nanoparticles, such as transport of genes and drugs for disease treatments, including cancer and infections. So, it is important to clarify if nanoparticles may represent a hazard to the environment and human health. In this study, we investigated the toxic potential and ability to induce DNA damage of different nanoparticles: four species of carbon nanotubes (NTC, NT, CS e MW), silver (AgNP) and nanoceria (CeO2-NP) nanoparticles. It was employed the somatic mutation and recombination test (SMART) in Drosophila melanogaster that detects the loss of heterozygosity of two genetic markers involved in the metabolic pathways of wing hairs formation - multiple wing hairs (mwh) and flare3 (flr3). In larvae, the proliferating of wings imaginal disc cells can produce hairs with mutant phenotypes expressed on the adult wings. Using the standard cross, third-stage larvae were treated with different concentrations of the nanoparticles until pupal stage. The wings of adult flies were examined microscopically for the identification of phenotypic abnormalities. In all concentrations the survival rates were higher than 90%, indicating the absence of chronic toxicity for nanoparticles evaluated. Using the conditional binomial test, the results of different treatments were compared with the respective negative control (distilled water), demonstrating no significantly increase in the NTC, NT and CS mutation and recombination frequencies (p>0.05) in mwh/flr3 genotype. In all carbon nanotubes tested, only the two higher concentrations of nanotubes MW (0.4 and 1 mg/mL) were able to induce genetic changes, mainly by mitotic recombination. The concentration of 10 mg/mL AgNP also promoted changes in the DNA and 61% of the phenotypic abnormalities were caused by recombination. The nanoceria was able to produce genotoxic effects at all concentrations tested (0.64-10 mg/mL). Overall, the mutational events were predominant, ranging from 46 to 72% of the total genotoxic effect induced by nanoceria, showing no dose-response relationship. In conclusion, our results demonstrated that carbon, silver and cerium dioxide nanoparticles have different genotoxic potential in D. melanogaster, so, another studies should be performed before any clinical and/or industrial application of nanoparticles.